Effects of dietary supplementation with lovastatin on feed digestibility, methane emission, carcass characteristics and meat quality of goat - Garba, Sani (2018)
Efforts including the use of feed additives and supplements to mitigate rumen methanogenesis were intensively researched but their low efficacy and sustainability have resulted in limited acceptance at farm level. Therefore, there is a need for the development of an effective CH4 mitigating agent which is not only cost effective but safer to both animals and consumers as well. Statin reduces the level of low-density lipoprotein cholesterol by effectively inhibiting 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase and has also been reported to reduce methanogensis and thus enteric CH4 production. However, it has been reported that administration of statin can cause side-effects such as myopathy. This research/thesis evaluated the effect of feeding naturally-produced lovastatin on feed digestibility, CH4 emission, carcass characteristics, meat quality, accumulation of lovastatin residues and possible skeletal muscle myopathy in goats fed with different dosages of naturally-produced lovastatin over three measuring periods (4-, 8- and 12-weeks). Therefore, experiments were conducted using four dietary treatments containing 0 (Control), 2 mg (Low), 4 mg (Medium) and 6 mg (High) per kg BW of naturallyproduced lovastatin fed to the experimental goats for 12 consecutive weeks under the same management conditions. In the first experiment, effective dosage of naturallyproduced lovastatin to reduce CH4 emission in long-term mitigation of emission of greenhouse gasses into the atmosphere using palm kernel cake (PKC) as a substrate incubated with Aspergillus terreus was determined. The results showed that lovastatin had no effect on feed digestibility. Enteric CH4 emissions per unit dry matter intake (DMI) decreased by 11% and 20.4%, respectively, for the 2 and 4 mg/kg BW groups and no further decrease in CH4 emission thereafter with higher lovastatin supplementation and minor effect on rumen microbiota The goats were slaughtered after 12 weeks of the feeding trial according to the halal procedure. Experiment two investigated the blood and histological parameters of the goats fed different dosages of naturally-produced lovastatin for any effect on animals’ physiology or health. No significant difference (p<0.05) in all the blood parameters tested except triglycerides (cholesterol, LDL, HDL) and granulocytes (basophil and eosinophil). However, histological study showed supplementation of naturally-produced lovastatin at 4 mg/kg BW and 6 mg/kg BW causes changes in histologic features. Thus, indicating the possibility of muscle myopathy. In order to safeguard public health, meat products must not contain residues associated with feed and drug residues that might constitute a health hazard. Thus, third experiment was conducted using HPLC and LCMS/MS methods to detect lovastatin residues. Lovastatin residues were detected in Longissimus thoracis et lumborum (LTL) muscle; liver and kidney samples from goats fed 6 mg lovastatin/kg BW and the residues were range between 0.01-0.03 μg/g which is far below the level recommended for hyper-cholesterol treatment in humans. The fourth experiment aimed at investigating the carcass characteristics, physico-chemical properties, storage stability and cholesterol content of meat from goats fed with different dosages of naturally-produced lovastatin. No differences were found in all the parameters measured except for full LW, hot and cold carcass weight, color, shear force and cholesterol content among the treatment groups. Meats in the medium and high treatments were more tender and had lower cholesterol levels. Supplementation of naturally-produced lovastatin at 4 mg/kg BW dose can effectively mitigate methane production and reduce cholesterol level at what can be regarded as safe for consumers.